An education rooted in two worlds: The Karen of northern Thailand - Jonni Odochao (2018)
In Karen culture, the family is traditionally the basic unit for the education of the child. In the early 1970s, when Jonni Odochao began to notice that children could not relate to their elders or respect them, he surmised that the problem stemmed from the modern education system and its increasing influence upon youth values, behaviour and ways of thinking. To counter this trend he set in place a two-pronged strategy. Inspired by an old Karen saying, a wide-ranging alliance of persons with complementary expertise was established to advocate legislative change. In addition, Karen culture was reflected upon and revived by integrating traditional knowledge into the curricula of local schools. For the Karen, the ultimate goal is to be better understood by the society at large and to re-establish their role as guardians of the forest. © UNESCO 2006.